2016
DOI: 10.1002/tox.22247
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MDA‐MB‐231 breast cancer cell proliferation and tumor growth by apigenin through induction of G2/M arrest and histone H3 acetylation‐mediated p21WAF1/CIP1 expression

Abstract: Apigenin (4',5,7-trihydroxyflavone), a flavonoid commonly found in fruits and vegetables, has anticancer properties in various malignant cancer cells. However, the molecular basis of the anticancer effect remains to be elucidated. In this study, we investigated the cellular mechanisms underlying the induction of cell cycle arrest by apigenin. Our results showed that apigenin at the nonapoptotic induction concentration inhibited cell proliferation and induced cell cycle arrest at the G2/M phase in the MDA-MB-23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(70 citation statements)
references
References 40 publications
8
52
0
2
Order By: Relevance
“…Histone acetylation is a valuable mechanism of epigenetic regulation. Therefore, Tseng et al suggested that apigenin inhibited breast cancer cell growth through the modulation of epigenetic regulation . In the present study, a remarkable cytotoxic effect of apigenin on MCF‐7 was detected.…”
Section: Discussionsupporting
confidence: 60%
“…Histone acetylation is a valuable mechanism of epigenetic regulation. Therefore, Tseng et al suggested that apigenin inhibited breast cancer cell growth through the modulation of epigenetic regulation . In the present study, a remarkable cytotoxic effect of apigenin on MCF‐7 was detected.…”
Section: Discussionsupporting
confidence: 60%
“…Possible mechanisms included induction of G 2 /M cell cycle arrest and epigenetic alterations. Apigenin inhibited HDACs, which induced acetylation of histone H3 in the p21 WAF1/CIP1 promoter region, leading to enhanced transcription of p21 WAF1/CIP1 [79]. Similar epigenetic effects were also found in prostate cancer.…”
Section: Experimental Studiesmentioning
confidence: 95%
“…Also, studies suggest that combining apigenin with other flavones such as genistein inhibited tumor growth by complexing with Cu (II), thereby significantly enhancing the antitumor properties [62]. In triple-negative breast cancer cells, apigenin results in epigenetic changes by inducing histone H3 acetylation, thereby decreasing cyclin A and cyclin B and increasing p21/Waf1/Cip1 levels [63]. A sub-cytotoxic concentration of apigenin inhibits IFN-γ-induced PD-L1 expression in MDA-MB-468 and 4T1 breast cancer cells, associated with reduced phosphorylation of STAT1, transiently at Tyr701 and persistently at Ser727.…”
Section: 0 Effect Of Apigenin In Various Human Cancersmentioning
confidence: 99%